Fluconazole impacts the extracellular matrix of fluconazole-susceptible and -resistant Candida albicans and Candida glabrata biofilms - Panariello, Beatriz Helena Dias; Klein, Marlise I. [UNESP]; Mima, Ewerton Garcia De Oliveira [UNESP]; Pavarina, Ana Cláudia [UNESP] (Taylor & Francis, 2018)
Background: Fluconazole (FLZ) is a drug commonly used for the treatment of Candida infections. However, β-glucans in the extracellular matrices (ECMs) hinder FLZ penetration into Candida biofilms, while extracellular DNA (eDNA) contributes to the biofilm architecture and resistance. Methods: This study characterized biofilms of FLZ-sensitive (S) and -resistant (R) Candida albicans and Candida glabrata in the presence or absence of FLZ focusing on the ECM traits. Biofilms of C. albicans American Type Culture Collection (ATCC) 90028 (CaS), C. albicans ATCC 96901 (CaR), C. glabrata ATCC 2001 (CgS), and C. glabrata ATCC 200918 (CgR) were grown in RPMI medium with or without FLZ at 5× the minimum inhibitory concentration (37°C/48 h). Biofilms were assessed by colony-forming unit (CFU)/mL, biomass, and ECM components (alkali-soluble polysaccharides [ASP], water-soluble polysaccharides [WSP], eDNA, and proteins). Scanning electron microscopy (SEM) was also performed. Data were analyzed by parametric and nonparametric tests (α = 0.05). Results: In biofilms, FLZ reduced the CFU/mL of all strains (p < 0.001), except for CaS (p = 0.937). However, the ASP quantity in CaS was significantly reduced by FLZ (p = 0.034), while the drug had no effect on the ASP levels in other strains (p > 0.05). Total biomasses and WSP were significantly reduced by FLZ in the ECM of all yeasts (p < 0.001), but levels of eDNA and proteins were unaffected (p > 0.05). FLZ affected the cell morphology and biofilm structure by hindering hyphae formation in CaS and CaR biofilms, by decreasing the number of cells in CgS and CgR biofilms, and by yielding sparsely spaced cell agglomerates on the substrate. Conclusion: FLZ impacts biofilms of C. albicans and C. glabrata as evident by reduced biomass. This reduced biomass coincided with lowered cell numbers and quantity of WSPs. Hyphal production by C. albicans was also reduced.
Keywords: Biofilm; Candida albicans; Candida glabrata; extracellular matrix; fluconazole; fluconazole-resistant